Schema complexity and valence elicited by country logos for tourism. Issue 3 (2nd July 2016) - Rodriguez, Lulu; Lee, Suman; Sar, Sela
Abstract: This study examined the influence of tourism logo design on people's cognitive responses. In an online survey, undergraduate students were exposed to the tourism logos of Australia, Indonesia, Mongolia, Kenya, Latvia and Malawi. The results showed that the logos of Australia and Indonesia elicited high schema complexity and positive valence among college students. The logos of Kenya and Mongolia rated high in schema complexity, but produced a negative valence. Malawi and Latvia elicited low schema complexity, but a positive valence. The findings suggest that effective meaning creation can overcome deficiencies in logo design.